Unemployment, Education, Health, and Poverty in Indonesia: Islamic Perspective - Yunita Yunita; Rosydalina Putri; zulaikah zulaikah (Keizai, 2026)
This study aims to analyze the influence of the open unemployment rate, educational attainment, and life expectancy on multidimensional poverty across 34 provinces in Indonesia from 2015 to 2024, through an Islamic economic perspective. The research employs a quantitative approach, utilizing numerical and statistical analysis to examine inter-variable relationships. Secondary data sourced from BPS-Statistics Indonesia is used, covering macro-level data for 34 provinces. The study utilizes panel data, combining time-series data from 2015 to 2024 with cross-sectional data from 34 provinces, resulting in a total of 340 observations. Partials results indicate that unemployment significantly increases poverty rates, while education plays a crucial role in reducing them. Conversely, life expectancy does not show a significant impact on economic productivity. These findings underscore the necessity of implementing the Maqashid al-Sharia concept to enhance welfare through educational advancement and job availability.